ANALISIS DESAIN UI/UX WEBSITE SAMSAT KALIMANTAN TIMUR DENGAN METODE DESIGN THINKING - Asfi Janatu; Warhana Nandyu; Yustian Servanda; Tri Sudinugraha (Jurnal Teknologi informasi dan Ilmu Komputer, 2026)
The East Kalimantan SAMSAT (Sistem Administrasi Manunggal Satu Atap) website serves as a crucial digital public service for motor vehicle tax payments and related services. However, suboptimal user experience (UX) and user interface (UI) often hinder accessibility and public satisfaction. This study primarily aims to analyze and identify UI/UX design constraints on the East Kalimantan SAMSAT platform, and to provide recommendations for improvements based on user perspectives. The applied method is Design Thinking, which includes five stages: Empathize, Define, Ideate, Prototype, and Test. The initial stage focused on data collection through observation, in-depth user interviews, and heuristic evaluation to uncover user needs and pain points. The analysis findings revealed issues such as complex navigation, inconsistencies in visual design, and lack of explicit information, all of which significantly increased user cognitive load. Based on these results, the study proposes specific design recommendations in the form of wireframe and mockup improvements. These recommendations focus on simplifying the user flow, increasing the consistency of UI elements, and developing a more intuitive search feature. This design proposal is expected to boost the effectiveness, efficiency, and user satisfaction of online SAMSAT services. These design recommendations were then validated during the testing phase through usability testing. Test results showed significant improvements in key metrics: the average task success rate increased to 90% and the task completion time decreased by 40%. These findings demonstrate that the systematic application of human-centered design is effective in bridging the gap between user needs and the quality of digital public services at the East Kalimantan SAMSAT.